Improving Students' Religious Character by Using Audiovisual Media in Islamic Education Learning at MIN 4 Aceh Selatan - Mazidah (Journal of Action Research in Islamic Education, 2025)
This study aims to improve students’ religious character through the use of audiovisual media in Islamic Education learning at MIN 4 Aceh Selatan. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 28 fifth-grade students. Data were collected through observation sheets, religious character assessment rubrics, interviews, and documentation. Quantitative data were analyzed using descriptive statistics to determine the percentage of improvement across cycles, while qualitative data were analyzed through reflective analysis to identify changes in students’ attitudes and learning engagement. The findings indicate a significant improvement in students’ religious character after the implementation of audiovisual media. In the pre-cycle stage, the average religious character score was 68.21 (moderate category), with only 46.4% of students achieving the minimum mastery criterion (≥75). In Cycle I, the average score increased to 76.35, with 71.4% mastery. After refinement in Cycle II, the average score reached 85.12, with 92.8% of students meeting the mastery criterion. Observational data also revealed increased student engagement, active participation, discipline in prayer practice, respect toward teachers and peers, and improved moral behavior during classroom activities. The results demonstrate that integrating audiovisual media in Islamic Education learning effectively enhances students’ religious character by providing contextual, visual, and emotionally engaging learning experiences. This study contributes to the growing body of research on innovative instructional strategies in Islamic Education and offers practical implications for teachers seeking to strengthen character education through technology-enhanced learning environments.